ГУМАНИЗМ ИДЕЯЛАРЫНЫҢ ИНСАН РУЎХЫЙЛЫҒЫН ҚӘЛИПЛЕСТИРИЎДЕГИ ӘҲМИЙЕТИ - Мамбеткаримов, Р.; Бийимбетов, Ж.; Абдиев, Б. (ILIM hám JÁMIYET, 2020)
Spirituality of a person especially its measures are described widely in this article. The specific humanistic peculiarities of a person, social life and personal phenomenon, model development of the society, the effects of ethics to personal life, mutual relations between traditions, customs and literature and significance of a person as a spiritual prominence are explained thoroughiy. These issues and their main meanings are analyzed from the phisological point of view.